A Multivariate Analysis of Contractual Saving - Reher, William C. (The Review of Economics and Statistics, 1966)
F LUCTUATIONS in economic activity depend not only on variation in investment but also on variation in saving. How flexible or inflexible saving will be depends partially on previous commitments to save. The concept of saving, has been defined ' by the Survey Research Center of the University of Michigan to include life insurance premium payments,2 payments into retirement or pension funds,3 and principal payments on mortgage debt.4 Non-contractual forms of saving may be called discretionary. All of the components included in the Survey Research Center's definition have common characteristics: (1) Each hinges on a previous contract limiting the possibility of spending on consumer goods. (2) The contractual commitment is of a long-term nature. Two factors would seem to make contractual saving relatively stable: (1) the habitual response to previous decisions, and (2) the economic loss suffered by prematurely discontinuing a long-term commitment to save. The primary purpose of this study is to search for the factors influencing the level of contractual saving. Tests of significance are applied by comparing the coefficients of the selected variables in multiple regressions with their respective standard errors. Our work is different and more comprehensive than the analysis of life insurance premiums by Professors Kreinin. Lansing. and Morgan.5 We are concerned with the aggregate amount of contractual saving rather than with only one of its components. Also, the population is divided into a low-income group and la high-income group with separate analyses for each. The analysis of contractual saving is becoming increasingly important since the trend of contractual saving as a per cent of total saving is upward. In 1949, contractual saving was almost as large as total saving since discretionary dissaving largely offset positive discretionary saving. In explaining aggregate contractual saving both for the high-income group and for the low-income group, our basic theory was clearly confirmed. Disposable income, marital status and the presence or absence of children, and educational level all proved to be significant.6 The power of their influence was in the order stated with disposable income dominant. Race did prove to be significant for the high-income group while age was significant within the lowincome group. Further details must wait.